The Effect of Financial Performance on ROA Projected as Profitability - Sasongko, Fusthathul Nur; Rachma, Elvira (Majapahit Journal of Islamic Finance and Management, 2021)
The study aims to determine the effect of financial performance on ROA, in which financial performance is indicated by the variables ROE (X1), NPF Gross (X2), BOPO (X3), and FDR (X4) in BRI Syariah (BRIS) Quarterly 2012-2019. The research data used secondary data and tested by regression test and then tested the classical assumptions consisting of normality test, heteroscedasticity test, multicolinearity test, and autocorrelation test. While the data analysis used multiple linear regression analysis. The results of the study indicate that of the four independent variables, only Gross NPF is not significant with a regression test value on ROA of 0.0929, which means that Gross NPF does not pass the test because the probability value is > 0.05.